The effects of screen use on children's health and development. (2nd February 2021) - Hancock, David
Abstract : Screen use by children has increased and starts at an earlier age; but in many cases evidence of the effects is not definitive. Dave Hancock reports on what is known, with some recommendations for advice for parents